The urban image and quality of life of the people from the district of Lurín - Velásquez Hidalgo, Oswaldo (2024)
Lurin is one of the receiving areas of the urban expansion of Metropolitan Lima with protected natural areas, archaeological heritage of long tradition and important for Lima and Peru, with tourist circuits, whose territorial wealth is also constituted by the southern coastal strip of Lima, providing by its location and extension, richness of flora and fauna of terrestrial and marine ecosystems. The objective of the research is to analyze the urban image and through this, the effect on the quality of life of the inhabitants of Lurin, The methodology is non-experimental design basic type, explanatory level. Results. The analysis of the surveys allows us to verify the lack of knowledge of the population on aspects related to the importance of the image of their area of residence and its impact on the quality of life of the inhabitants. Conclusions. The lack of planning is an important factor for an urban image integrated by elements such as identity, formal diversity, visual alternatives, orientation, clarity in access and circulation, affecting the quality of the urban image, which is deteriorating. The urban image plays an important role, because through it, mental, visual and objective integration of the city or space is generated, because when all the elements that integrate it are clearly configured, it can affect the comfort and in general the welfare of people, due to deficient basic services, mainly water, sewage, environmental quality, as well as economic and cultural factors.